SEMANTIC EXPRESSIONS OF POSTERS OF COVID-19 PANDEMIC; TRIBUNNEWS.COM (ELATICS JOURNAL, 2023)
Covid-19 is becoming pandemic of such magnitude that it has caused a global issue to society. The research aim is to know the effectiveness of posters of Covid-19 Pandemic which taken from Tribunnews.com Mass Media. The research uses Semiotic method which is used to uncover the semiotic meaning from the poster expressions of Covid-19 Pandemic. The research aims to find out signs that represent the posters; to find out meanings that contain on poster. This study uses qualitative method. The findings of the research shows that there are 3 meaning on the poster namely semantic lexical, grammatical and contextual. Each sign has meaning. The way illustrator attracting audience’s attention is very smooth. Although the poster looks simply, the visual and the way s/he uses the colours. By the written, the slogan, the colour, and the design, the illustrator is successful in building people’s enthusiasms on the posters.